The Effect of Product Quality and Price on Consumer Loyalty at “Jeda Coffee & Space” in Bekasi City, West Java - Aulia Ananda; Imam Wibowo; Richard (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to determine whether or not there is an influence of product quality and price on customer loyalty both simultaneously and partially at Jeda Coffee & Space. The research method was carried out on 68 customer respondents with accidental sampling technique, data collection using a questionnaire with a semantic differential scale, and analyzed using SPSS version 25. Determination of the number of samples using the Lemeshow formula because the population size is not known with certainty. The results of the study indicate that product quality and price each influence customer loyalty, as well as simultaneously product quality and price have a positive and significant effect on customer loyalty. The results of the respondent's assessment gave a good assessment, namely dominant statements strongly agree and agree on the quality of the product and price provided by Jeda C&S. Recommendations for product quality are to continue to improve the performance aspect, namely ensuring that every customer order is always in accordance with expectations in terms of taste, appearance, and presentation. On the price side, it is proposed that Jeda Coffee & Space provide attractive promotions, and strengthen customer loyalty through programs such as membership or rewards. This recommendation is so that customers feel satisfied and tend to make repeat purchases and improve customer experience so that they do not easily move to other coffee shops that are growing in the Bekasi area.